Data Migration Techniques within Cloud Computing: A Comprehensive Analysis - kaur, Kiranbir; kumari, Harpreet (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is becoming need of the hour for providing resources at pay per use to users. Data migration is the mechanism of transferring data to cloud where it is stored in virtual environment. It is key consideration behind the active data migration process where users storage is preserved. Up gradation or consolidation is accomplished within cloud using the application of data migration. During migration process, parameters are required to be validated. These parameters involve downtime and migration time. As the migration is finished, organization validates the transfer process statistically. The accuracy of data migration process is also questioned by the organization. in case accuracy is low migration is rejected. Data and pre-processing and cleaning facilities improve data quality via removal of unnecessary or repeated data. This paper presents the distinct data migration techniques within cloud used to transfer Users data to data centers for effectively storing and servicing the user. Techniques presented are compared comprehensively for future enhancements.